(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
“Rural development is an essential part of the overall development of India because seventy percent of the Indian population depends upon agriculture and lives in rural areas. This study is related to measuring the performance of long-term rural cooperative banks of India such as SCARDBs, and PCARDBs. This study is based on secondary sources that is collected from the published annual reports of RBI for the financial year ended 2016 to 2023. Spread ratio, burden ratio, profitability ratio, Number of branches, deposit, loan and advances, capital and research, NPA ratio to total assets, and recovery to demand ratio are measured to evaluate the performance of SCARDBs, and PCARDBs bank. The financial indicators of long-term rural cooperative banks such as Capital & reserve, deposits, and advances have shown growth but it is not a significant growth. There is no growth in the number of branches in SCARDBs. The result showed that SCARDB’s bank performance is better as compared to PCARDBs.The findings of this study concludes that these banks play a very important role in the development of rural areas.